Self-sustainability of phosphorus cycle in rubber (Hevea brasiliensis) plantations: Annual recycling through litter and removal through latex - Jessy, M.D.; Sasidharan Nair, A.N.; Bai, M. Meera; Rajendran, P.; Punnoose, K.I. (Journal of Plantation Crops, 2009)
Low phosphorus availability is one of the main soil factors limiting forest productivity in tropical and subtropical regions. Rubber (Hevea brasiliensis) trees are predominantly cultivated in warm humid tropics and the self-sustainability of rubber plantation with respect to phosphorus nutrition was studied in a PB 217 plantation planted in 1984 and received phosphorus at various levels (0, 10, 20, 30 and 40 kg ha-1yr-1) from 1998 onwards. All the treatments received nitrogen and potassium uniformly at the rate of 30 kg ha-1yr-1. Before the commencement of the experiment all the trees were uniformly manured with nitrogen, phosphorus and potassium. Yield of latex, recycling of P through litter and removal through latex were quantified during 2003-04. Recycling and removal of other nutrients were also quantified. Yield of latex was not influenced by the levels of P applied. Content of P in litter and latex and quantity of litter added were also not influenced by the levels of P. Recycling and removal of other major and micronutrients were also comparable in all the treatments. Annual recycling of P through litter was marginally greater than removal through latex whereas, recycling of other nutrients was substantially higher than their export through latex. The data indicate the self-sustainability of P cycle in a mature rubber plantation adequately supplied with phosphorus during the actively growing phase.